Fiscal strategies amid global uncertainty: Strengthening indonesia’s economic and investment resilience through a national supply chain resilience roadmap - Ginsu, Mesakh Roi Pratama; Julianti, Laura Amaria Dwiputri; Haris, Fachry (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: When global conditions are unstable, policy-making driven by urgency and efficiency is necessary to maintain national stability, particularly in Indonesia. In the context of a trade war, the key threats to address are declining investment and weakening economic activity. One of the instruments that can be utilized is fiscal policy. Nevertheless, fiscal resources are limited. Hence, the main questions to be answered in this article are: (1) What’s the most significant sector that affects economic growth and investment performance? (2) What’s the strategy and solution that can be implemented to achieve the fiscal efficiency point? Methods: To answer the first main question, use a literature review. All literature used in this article is from the Scopus index database. On the other hand, the authors also apply the adaptation of the National Supply Chain Resilience Roadmap (NSCRR) method while combining it with a literature review to formulate a fiscal policy strategy that ensures efficient implementation. Findings: Supported by existing literature, the authors identifies infrastructure as the sector with the highest significance in boosting economic growth and investment in Indonesia. Additionally, authors propose three complementary technical strategies to ensure the efficient implementation of fiscal policy. These three strategies include the Fiscal Deficit Reduction and Accountability Reform System (FIDARS), the National Integrated Smart Government System (NISGS), National Infrastructure Technology Transfer Scheme (NITTS) Conclusion: To attract FDI, investment in public goods such as infrastructure is empirically proven to have a more massive impact and is more efficient due to the vast fiscal multiplier that is greater than in other sectors. Yet, the fiscal allocation needs to be implemented strategically and efficiently by using the three strategies mentioned above. Novelty/Originality of this article: The new adaptation of NSCRR to create fiscal strategies has not been written before.